Psychosocial problems among school going adolescents in Ghorai sub metropolitan city of Dang - Devkota, Sapana; Adhikari, Kishor; Ghimire, Amrita; Koirala, Subash; Chhetri, Mamta (Journal of Chitwan Medical College, 2020)
Background: A psychosocial problem is a mental illness caused or influenced by life experiences, as well as maladjusted cognitive and behavioral processes. Psychosocial problems i.e. internalizing disorders, externalizing disorders and substance abuse are more prevalent among adolescents because of their rapid physical and physiological changes that occur in their body during this stage. The aim of the study was to identify the magnitude of psychosocial problems among school-going adolescents. Methods: Present study was a descriptive cross-sectional study conducted in the ward no. 15 of Ghorahi sub metropolitan city of Dang District, Nepal. A total of 325 adolescents were chosen from multi-staged random sampling. Pre-tested self-administered questionnaire was used to collect data. Part I and part II of questionnaire was self-constructed and Part III was adopted from standard tool of Youth Pediatric Symptoms Checklist. Descriptive (percentage, frequency, interquartile range and minimum and maximum values) and inferential analysis (chi-square test) was done through this IBM SPSS software version 20. Results: The prevalence of psychosocial problems among school going adolescents was 26.8%. Socio-demographic characteristics such as age, ethnicity, occupational status of respondent’s father and mother were found to be significantly associated with psychosocial problems. The relation with teacher and academic grade of respondent were found to be highly associated with psychosocial problems. Conclusions: The study reported an alarming situation of psychosocial problems among adolescent students in Nepal where more than one quarter of participants found having psychosocial problems. The study may suggest the need of proper parenting and maintenance of an appropriate level of teacher-student relationship.